Heredity and Otosclerosis: A Review - RS, Greval; Singh, Bhagat (Journal of All India Institute of Speech and Hearing)
A genealogical tree is presented of a family in which the dominant heredity of clinical otosclerosis was traced through three generations. Recent hypotheses for hereditary transmission of the disease have been advanced and evaluated. Chromosomal changes in otosclerotic subjects have been found by different workers to be conspicuously absent. Therefore the most convenient, and practical, way of ascertaining the exact mode of genetic ransmission in otosclerosis is through large-scale family studies. This particularly holds good for a vast country like India. The most recent genetic studies in the field indicate a polygenic and probably multifactorial mode of heredity of otosclerosis.